Qada’ Dan Qadar Perspektif Al-Qur’an Hadits dan Implikasinya Terhadap Pendidikan Agama Islam - J. Nabiel Aha Putra; Moch. Ali Mutawakkil (J-PAI: Jurnal Pendidikan Agama Islam, 2020)
Something that happens to humans is that God's will is very true, but every human being also has his own will. So that in education students can change learning outcomes by continuing to learn and make a change of changes that will run in harmony and straight with the will and decision of God. The study aims to analyze the impact of the beliefs of God's will and provisions on the behavior of students. This research is qualitative in nature and uses literature study method. The results of the analysis show that the will and provisions of Allah make humans more obedient to Allah with more optimism, and can understand the wisdom of destiny itself. The implication of qada and qadar beliefs on Islamic religious education is the inclusion of righteous deeds in students. Based on these results, it can be concluded that belief in qada and qadar Allah in students has a very positive impact, one of which is doing good deeds in their daily behavior which can also be called al-Akhlaq al-Karimah or akhlaq mah easily.